(untitled) (Research, Society and Development, 2021)
The present study aimed to know the profile of mammograms performed in Campina Grande - PB, in the period from 2015 to 2019. This is an explanatory documentary study with a quantitative approach. The research was carried out in the DATASUS database, during the month of October 2020, the universe of research was constituted of the reported cases of mammography in the state. The sample consisted of the number of screening and diagnostic mammograms performed in the municipality. There was a prevalence of screening mammograms in 2015 among women aged 40- 49 years (3,638; 41.2%), as well as in 2016 (3,456; 39.9%), however, in 2017 (3,291; 38.8%), 2018 (3,417; 39.7%) and 2019 (3,921; 39.3%) the prevalence occurred among those aged 50-59. The age group with the lowest prevalence corresponded to women aged 60-69 years. Regarding the proportional distribution of BI-RADS, according to clinical indication, the most expressive results were shown in the BI-RADS 2 category, followed by BIRADS 1 and 0. In the variable on the number of nodules, greater predominance of sizes ≤ 10mm and ≤11-20mm both on the right and on the left breast, and between the age group of 40 to 59 years in both breasts. It is hoped that this work can contribute to future studies and clarify essential information for the area of ​​screening. In addition, to provide greater knowledge about the profile of mammograms in the current city in search of improvements in screening, contributing to the lower rate of breast cancer.